Efektivitas Layanan Bimbingan Kelompok denganMemahami Ayat-Ayat Alquran untuk Meningkatkan Motivasi Belajar Siswa di Mts. Alfurqan Padang - N, Dyla Fajhriani; S, Neviyarni; Efendi, Mawardi (Konselor, 2015)
This research were to see the difference between learning motivation of students in the experimental group taught by applying group guidance service through understanding the verses of Alquran in pretest and posttest, the difference between learning motivation of the students in the experimental group taught by applying group guidance service throught understanding the verses of Alquran and that of the students in the countrol group taught by applying group guidance service without understanding the verses of Alquran in pretest and posttest, and the difference between learning motivation of the students in the experimental group guidance services throught understanding the verses of a Alquran and that of students in the control group guidance taught by applying group guidance service throught understanding the verses of Alquran. This research aplied pretest posttest control group design. Throught this research, the researcher gave a pretest to both sample groups. They then got different treatment. After the treatment was done, a posttest was administrated to both groups. This kind of eksperimental researches would ensure that the difference (if the result is different) occurs between the experimental group and the control group is as the influence of the treatment given. The resesarch findings indicated that learning motivation of the students taught by applying group guidance service throught understanding the verses of Alquran increased.